Optimization Of Fixed Assets Through State Property Management (Study At The Indonesian Center For Agricultural Biotechnology And Genetic Resources Instrument Standard Testing) - Lutfi, Lutfi Padhil; Indupurnahayu, Indupurnahayu; Aminda, Renea Shinta (Universitas Ibn Khladun Bogor, 2025)
This study aims to analyze:1) Implementation of fixed asset utilization, 2) Implementation of accuracy and precision of fixed asset inventory, 3) Strategy of fixed asset security and maintenance procedures, 4) Implementation of fixed asset administration applied to the optimization of fixed assets through state property goods administration. The method used is descriptive case study with a qualitative approach. The results of the study show: 1) The management and utilization of state property assets at BBPSI Biogen have shown progress but are not yet fully optimized. Challenges include incomplete asset mapping and limited third-party collaboration. However, the Use Status Determination and rental-based asset utilization have been carried out in compliance with regulations, contributing to increasing Non-Tax State Revenue. Supervision and control are conducted regularly, supporting efficient management. 2)Inventory activities are well-organized, with no abandoned assets, proper labeling (codification), and clear records—though inventory updates for machinery are hampered by limited human resources. 3)The security and maintenance strategies for state property are fairly optimal, incorporating administrative, physical, and legal safeguards. Maintenance is carried out in a scheduled and documented manner, preventing loss and damage. 4)Overall, the administration of assets has been systematic, transparent, and aligned with Government Accounting Standards, positively impacting the optimization of fixed asset management.